Catalogue of Good Practices of Sustainable Culinary Heritage Experiences in Mediterranean Area - Šmid Hribar, Mateja (ZRC SAZU, Založba ZRC, 2018)
The Catalogue of Good Practices of Sustainable Culinary Heritage Experiences in Mediterranean Area provides a detailed description of 18 culinary experiences from 8 different Mediterranean countries: Italy, France, Spain, Portugal, Croatia, Greece, Cyprus and Slovenia. The good practices cover various types of culinary experiences, namely tourist sites networks dedicated to food or culinary products, services connected to food products, professional activities linked to food highlighted through a touristic activity, culinary events, specific tourist sites dedicated to food or culinary products. The Catalogue reveals how culinary experiences work, who is involved, and what are the "ingredients" which make them successful. Each culinary experience is described through a story in which you will find valuable information on: local (territorial) anchoring and relationship to heritage, organising and managing aspects, relation to existing policies and strategies, sustainability aspects, innovative aspects, monitoring and stakeholders' views.